Proceedings of the First International Conference Economic and Business Management 2016 2016
DOI: 10.2991/febm-16.2016.36
|View full text |Cite
|
Sign up to set email alerts
|

The Study of the Momentum Effect and the Reversal Effect On the Chinese Stock Market--Based on the Data of Chinese A-Share Market

Abstract: Momentum and reversal investment strategy are based on cross trade mechanism, which was not available until Aril, 2010 in China. Since then, countless papers in this area have been benefited from a mass amount of data. Using the stock market data since April 2010, this paper sets focus on the existence of the momentum effect and reversal effect on Chinese stock market. From the empirical research results, we find that there exist the short-term momentum effect and the mid-term reversal effect on Chinese stock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…At the same time, it is important to explain that our conclusions are different from those of Wang et al (2006) and Deng et al (2021), who find that stocks with low volume have stronger momentum effects in China. We believe that this could be attributed to the fact that industry momentum is different from individual stock momentum.…”
Section: Industry Momentum and Trading Volume 1139contrasting
confidence: 94%
See 1 more Smart Citation
“…At the same time, it is important to explain that our conclusions are different from those of Wang et al (2006) and Deng et al (2021), who find that stocks with low volume have stronger momentum effects in China. We believe that this could be attributed to the fact that industry momentum is different from individual stock momentum.…”
Section: Industry Momentum and Trading Volume 1139contrasting
confidence: 94%
“…It is notable that the conclusion is not widely accepted. For example, some studies find that low-volume stocks have stronger momentum effects than high-volume stocks in the Chinese stock market due to stock price manipulation (Wang et al, 2006;Deng et al, 2021). Stock price manipulation refers to the manipulator buying stocks at a low price to raise the stock price, while making the trading volume increase, and then selling the stock at a high price, resulting in the reversal of stock returns.…”
Section: Industry Momentum and Trading Volume 1139mentioning
confidence: 99%
“…A variety of empirical research studies have been conducted on various emerging stock markets. Zeng and Liu (2016) provided an empirical study of the momentum effect and the reversal effect on the Chinese stock market based on Jegadeesh and Titman (1993) methods and concluded that there exist the short term momentum and mid-term reversal effect. Henker et al (2010) examined momentum effect in Australian equity market and concluded that there is no evidence for a consistent momentum effect in the Australian equity market since the late 1970s.…”
Section: Literature Reviewmentioning
confidence: 99%